Simulation of the model predictive control applied to a combined cycle plant - Nieto Chaupis, Huber (2016)
We present the simulation of the application of the Model-based Predictive Control (MPC) of the drum level in a Combined Cycle Plant in order to minimize the time for reaching the highest capacity of plant, around 225 MW. In contrast to others control techniques, our simulation yields that the MPC has shown capabilities as to reach its expected power in about 40 minutes before than PID, time which normally takes the whole industrial process under this control. In the present study, we have tested up to three different reference functions in order to compare performance during the drum level control. According to the simulations, the MPC working together with these reference functions is seen to be promising in the sense of providing efficiency to the plant from the startup until the time when system is reaching 225 MW. We have also calculated a minor discrepancy of order of lees than 5%.